Strengthening transparency and performance: The role of independent commissioners in enhancing CSR disclosure's impact on firm performance - Septiany, Sheila; Jurnali, Teddy; Antonia Sim, Cicilia; Suparman, Meiliana; Wati, Erna (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Purpose – This study examines the effects of corporate social responsibility (CSR) disclosure on firm performance measured by Return on Equity (ROE), while examining the moderating role of independent commissioners in strengthen this relationship.Design/methodology/approach – This research uses data obtained from all publicly listed companies on the Indonesia Stock Exchange, comprising 514 firm-year observations from 2018 to 2022. Employing moderated regression analysis model, the study evaluates the direct and moderating effects within the proposed research framework.Findings – The findings reveal that CSR disclosure is positively and significantly related to the firm performance. In addition, independent commissioners are shown to strengthen the relationship, where more independent and objective supervision increases the effectiveness of CSR and attracts investor confidence.Research limitations/implications – This study aggregates CSR disclosure without differentiating its parts and does not account for the features of independent commissioners, such as knowledge or tenure. Future studies should explore these dimensions and conduct comparative or longitudinal studies to enhance the understanding of CSR's impact on financial performance.Practical implications – This study provides guidance for company management to improve CSR strategies by enhancing the oversight quality of independent commissioners. The findings also suggest that policymakers and professional institutions should focus on strengthening the competence and accountability of board members through evaluation frameworks and training programs, to ensure effective governance in CSR practices and long-term firm performance.Originality/value – This study offers a new perspective by examining the moderating role of independent commissioners in the CSR to financial performance relationship in Indonesia, using a more detailed CSR disclosure measure based on the GRI 2021 framework. It provides practical and academic insights into governance and sustainability in emerging markets.